Challenges in the acute management of profound hyponatremia presenting with severe symptoms. Issue 4 (7th August 2016) - Mamoojee, Yaasir; Mukhtar, Rasha
ABSTRACT: Currently available guidelines in the acute management of severely symptomatic hypotonic hyponatremia vary in their approach to the use of hypertonic saline. In the acute setting, deciding on when to implement available treatment algorithm using hypertonic saline may be difficult, given that the duration of hyponatremia and potential alternative diagnoses presenting with similar symptoms may be hard to establish promptly. We present the case of a young female with symptomatic profound hyponatremia who subsequently developed osmotic demyelination syndrome due to rapid overcorrection of serum sodium concentration. We discuss the interplay between the dynamic pathophysiological processes responsible for hypotonic hyponatremia in adrenal insufficiency and conduct a detailed analysis of currently available guidelines to highlight the challenges in acute and reactive treatment in clinical practice.